Hollow annular FeSe2-coated NC composite material as well as preparation method and application thereof

Through hydrothermal synthesis and controllable selenization process, hollow ring FeSe2@NC composite material was prepared, and the volume expansion problem of FeSe2 material during charge and discharge was solved by using nitrogen-doped carbon coating, achieving excellent electrochemical performance and structural stability.

CN119764389APending Publication Date: 2025-04-04NINGDE NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411949117.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing FeSe2 composite materials have volume expansion and structural powdering during charging and discharging, which affects the electrochemical performance, and are complex in the preparation process and have high cost.

Method used

Through hydrothermal synthesis and highly controllable selenization process, FeSe2@NC composite material with hollow ring structure was prepared, and nitrogen-doped carbon was used as the cladding layer to alleviate volume expansion and improve electrochemical performance.

Benefits of technology

This material exhibits excellent electrochemical properties in the negative electrode application of sodium ion battery, and can maintain a high specific capacity after 200 cycles, and significantly improve structural stability and cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764389A_ABST
    Figure CN119764389A_ABST
Patent Text Reader

Abstract

The invention provides a hollow annular FeSe2-coated NC composite material and a preparation method and application thereof.The composite material is composed of an external nitrogen-doped carbon layer and internal FeSe2 nanoparticles wrapped with the external nitrogen-doped carbon layer and is of a unique hollow annular structure; the preparation method comprises the following steps: preparing a Fe2O3 precursor by a hydrothermal method, adding the Fe2O3 precursor into a Tris buffer solution for ultrasonic dispersion, adding dopamine into the solution, stirring for a long time at normal temperature, separating, washing, and drying to obtain Fe2O3 (at) PDA; fe2O3 (at) PDA and Se powder are selenized at the two ends of a porcelain boat according to a certain mass ratio in the atmosphere full of Ar / H2, and a FeSe2 (at) NC composite material is obtained; as a sodium ion battery negative electrode material, the composite material shows excellent electrochemical performance, and the specific capacity of 421.2 mAh g <-1 > can still be kept after 200 times of circulation under the current density of 5A g <-1 >, so that the material has the electrochemical performance with higher application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrode material technology, in particular to a hollow ring-shaped FeSe 2 @NC composite materials and their preparation methods and applications. Background Art

[0002] Lithium-ion batteries have been successfully used in real life and dominate the market due to their high energy density. However, the high price of lithium and the uneven distribution of resources limit their application in large-scale energy storage. Sodium-ion batteries have been widely studied because their working principles are similar to those of lithium-ion batteries, and sodium resources are abundant and evenly distributed. However, the rapid capacity decay during charging and discharging and the unstable cycle rate performance hinder the large-scale development of sodium-ion batteries. Therefore, seeking suitable electrode materials has become an urgent problem to be solved. Among the negative electrode materials, iron diselenide has shown great potential in the field of sodium-ion batteries because of its high theoretical specific capacity and good electrochemical reversibility. However, how to alleviate the volume expansion and structural pulverization of this material during the sodium insertion and extraction process is the focus and difficulty of current research. Wang et al. successfully synthesized FeSe with oxygen vacancies. 2 Nanosheets are used as negative electrodes for sodium-ion batteries. -1 After 700 cycles at the current density of 268.6 mAh g -1 The discharge specific capacity and cycle performance were improved. Chen et al. synthesized FeSe with nitrogen-doped carbon shell and MXene coating through multi-step structural design. 2 @NC@MXene composite materials, used as negative electrodes for sodium-ion batteries, have shown excellent rate and cycle performance. Ren et al. synthesized graphene-coated three-dimensional flower-like FeSe using a complex solvent-induced method combined with hydrothermal and high-temperature carbonization. 2 / rGO-EG composite material, the material at 1A g -1 After 1000 cycles at a current density of 400 mAh g -1 The discharge specific capacity of FeSe 2 The composite material has few structural active sites and experiences volume expansion during the charge and discharge process, which affects the electrochemical properties of the electrode. In addition, the preparation process is complex and the cost is high. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a coating layer based on a nitrogen-doped carbon matrix, and FeSe with a hollow ring structure is prepared by a simple hydrothermal synthesis method and a highly controllable selenization process. 2@NC material; this special structure not only provides more active sites for sodium storage applications, but also greatly alleviates the volume expansion of the negative electrode material during the charging and discharging process, showing excellent electrochemical performance.

[0004] The first aspect of the present application provides a hollow ring-shaped FeSe 2 @NC composite material, the composite material consists of an outer nitrogen-doped carbon layer encapsulating the inner FeSe 2 The composite material is composed of nanoparticles and has a hollow ring structure.

[0005] In any embodiment, the composite material is composed of an outer nitrogen-doped carbon layer, encapsulating an inner FeSe 2 It is composed of nanoparticles and presents a unique hollow ring structure with a particle size of 180-220 nanometers.

[0006] The second aspect of the present application also provides a hollow ring-shaped FeSe 2 The preparation method of the @NC composite material comprises the following steps:

[0007] S1, synthetic Fe 2 O 3 Precursor, adding the precursor into a buffer solution for ultrasonic dispersion, then adding dopamine into the solution and stirring at room temperature to obtain a brown-red precipitate-like separation;

[0008] S2, wash the brown-red precipitate with deionized water and ethanol several times and then put it into an oven to dry to obtain Fe 2 O 3 @PDA;

[0009] S3, will Fe 2 O 3 @PDA and Se powder were placed at both ends of the porcelain boat and selenized in a tube furnace to obtain a hollow ring structure of FeSe 2 @NC.

[0010] In any embodiment, in step S1, Fe 2 O 3 Synthesis of precursors:

[0011] S11, add a certain amount of ferric chloride hexahydrate to deionized water and stir, add sodium sulfate and sodium dihydrogen phosphate dihydrate after fully dissolved, stir until a uniform mixed solution is formed, transfer to a 200 mL reaction kettle, put into an oven, react at 200-250°C for 8-12 hours to obtain a precipitate, wash with deionized water and alcohol by centrifugation several times, and finally dry to obtain a hollow ring structure of Fe 2 O 3 Precursor.

[0012] In any embodiment, the amount of ferric chloride hexahydrate added is 6.3-6.5 g / L, the amount of sodium sulfate added is 0.14-0.16 g / L, and the amount of sodium dihydrogen phosphate dihydrate added is 28-31 mg / L, which represents the amount of substance added in 1L of the mixed solution; the mass ratio of ferric chloride hexahydrate, sodium sulfate and sodium dihydrogen phosphate dihydrate added is 92-100:4-5:1, and the preferred addition ratio is 96:4.4:1; too much or too little addition of sodium dihydrogen phosphate dihydrate synthesized Fe 2 O 3 The precursor will not present a hollow ring structure.

[0013] Too low a reaction temperature will result in incomplete reaction of the raw materials, while too high a temperature will result in uneven morphology of the prepared precursor.

[0014] In any embodiment, step S1, the precursor is added to a buffer solution containing Tris with a pH value of 8.0 to 9.0 for ultrasonic dispersion. The pH value is controlled between 8.0 and 9.0, which is weakly alkaline, which is conducive to the subsequent self-polymerization of PDA to coat Fe 2 O 3 Precursor surface.

[0015] In any embodiment, step S1, the Fe 2 O 3 The mass ratio of the precursor to dopamine is 1:0.6-1.2. Dopamine is added to the solution and stirred continuously at room temperature for 10-18 hours to obtain a brown-red precipitate-like separation. Adding too much dopamine will result in a thicker nitrogen-doped carbon layer, thereby affecting the cycle rate performance, while adding too little dopamine may result in failure of the nitrogen-doped carbon layer to be coated.

[0016] In any embodiment, in step S2, Fe 2 O 3 @PDA is dried at a constant temperature of 60℃~80℃ for 5~10h. If the drying temperature is too low, the product will contain moisture, affecting the subsequent selenization experiment. If the temperature is too high, the product will seriously agglomerate, which is not conducive to the selenization reaction.

[0017] In any embodiment, in step S3, Fe 2 O 3 @PDA and Se powder are placed at both ends of the porcelain boat in a mass ratio of 1:4-8. Too little Se powder will cause Fe 2 O 3 @PDA selenization is incomplete; if too much is added, there will be residual molten Se mixed in the target sample FeSe 2 @NC, difficult to remove cleanly.

[0018] In any embodiment, in step S3, the Fe2 O 3 @PDA and Se powder in a porcelain boat filled with Ar / H 2 In a tubular furnace with an Ar / H atmosphere, the proportion of hydrogen can be between 5% and 10%. A low hydrogen content is not conducive to the synthesis of the target product, while a high hydrogen content is prone to safety problems in the experiment. 2 (95%:5%); keep the temperature at 500-600℃ for 4-6h, and control the heating rate at 1-5℃ / min for selenization treatment, and finally obtain FeSe with hollow ring shape. 2 @NC composite material; The morphology of the composite material can be well maintained within the above temperature range, while a heating rate that is too slow will lead to a slow selenization reaction and an insufficient reaction, while a heating rate that is too fast will destroy the morphology and structure of the material.

[0019] A hollow ring FeSe 2 @Application of NC composite materials, composite materials as sodium ion negative electrode active materials.

[0020] The beneficial effects of the present invention are: the FeSe 2 The NC composites were prepared by a simple hydrothermal synthesis method and a highly controllable selenization process to obtain FeSe with hollow rings. 2 @NC material. This material exhibits excellent electrochemical performance when used as a negative electrode for sodium-ion batteries: -1 After 200 cycles at a current density of 421.2 mAh g -1 The excellent performance is inseparable from its unique hollow ring structure, which not only provides more active sites for sodium storage applications, but also the nitrogen-doped carbon coating on the surface of the material effectively alleviates the volume expansion of the negative electrode material during the charge and discharge process, thus giving the material more potential electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The Fe provided in the embodiment of the present invention 2 O 3 XRD characterization of the precursor.

[0022] Figure 2 The Fe provided in the embodiment of the present invention 2 O 3 SEM image of the precursor.

[0023] Figure 3 It is Fe provided in the embodiment of the present invention 2 O 3 @SEM image of PDA.

[0024] Figure 4The FeSe provided by the embodiment of the present invention 2 XRD characterization diagram of @NC.

[0025] Figure 5 The FeSe provided by the embodiment of the present invention 2 @SEM image of NC.

[0026] Figure 6 It is FeSe 2 and FeSe 2 @NC electrode material rate performance diagram at different current densities in the voltage window of 0.1~3.0V.

[0027] Figure 7 It is FeSe 2 and FeSe 2 @NC electrode material has a voltage window of 0.1-3.0V and a current density of 5A g -1 Cyclic performance diagram after 200 cycles under the conditions of .

[0028] Figure 8 It is FeSe 2 and FeSe 2 Nyquist plot after @NC cycle. DETAILED DESCRIPTION

[0029] The hollow ring FeSe nanostructured ... 2 @NC composite materials, preparation methods and application methods thereof. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0030] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0035] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0036] In one embodiment of the present application, the present application proposes a hollow ring-shaped FeSe 2 @NC composite material, the composite material consists of an outer nitrogen-doped carbon layer encapsulating the inner FeSe 2 The composite material is composed of nanoparticles and has a hollow ring structure.

[0037] In some embodiments, the composite material has a particle size of 180-220 nanometers.

[0038] In another embodiment of the present application, the present application proposes a hollow ring-shaped FeSe 2 The preparation method of the @NC composite material comprises the following steps:

[0039] S1, synthetic Fe 2 O 3 Precursor, adding the precursor into a buffer solution for ultrasonic dispersion, then adding dopamine into the solution and stirring at room temperature to obtain a brown-red precipitate-like separation;

[0040] S2, wash the brown-red precipitate with deionized water and ethanol several times and then put it into an oven to dry to obtain Fe 2 O 3 @PDA;

[0041] S3, will Fe 2 O 3 @PDA and Se powder were placed at both ends of the porcelain boat and selenized in a tube furnace to obtain a hollow ring structure of FeSe 2 @NC.

[0042] In some embodiments, in step S1, Fe 2 O 3 Synthesis of precursors:

[0043] S11, add a certain amount of ferric chloride hexahydrate to deionized water and stir, add sodium sulfate and sodium dihydrogen phosphate dihydrate after fully dissolved, stir until a uniform mixed solution is formed, transfer to a 200 mL reaction kettle, put into an oven, react at 200-250°C for 8-12 hours to obtain a precipitate, wash with deionized water and alcohol by centrifugation several times, and finally dry to obtain a hollow ring structure of Fe 2 O 3 Precursor.

[0044] In some embodiments, the amount of ferric chloride hexahydrate added is 6.3-6.5 g / L, the amount of sodium sulfate added is 0.14-0.16 g / L, the amount of sodium dihydrogen phosphate dihydrate added is 28-31 mg / L, and the mass ratio of ferric chloride hexahydrate, sodium sulfate and sodium dihydrogen phosphate dihydrate added is 92-100:4-5:1.

[0045] Add in proportion to prevent excessive / insufficient addition of some raw materials, resulting in Fe 2 O 3 The precursor cannot be synthesized.

[0046] In some embodiments, in step S1, the precursor is added to a buffer solution containing Tris with a pH value of 8.0 to 9.0 and then ultrasonically dispersed.

[0047] The pH value was controlled between 8.0 and 9.0, which was weakly alkaline, and was conducive to the subsequent self-polymerization of PDA and its coating on Fe 2 O 3 Precursor surface, ultrasonic dispersion ensures Fe 2 O 3 The precursor is evenly dispersed in the solution, which is conducive to the subsequent PDA coating on the Fe 2 O 3 Precursor surface.

[0048] In some embodiments, step S1, the Fe 2 O 3 The precursor and dopamine are in a mass ratio of 1:0.6-1.2. Dopamine is added to the solution and stirred continuously at room temperature for 10-18 hours to obtain a brown-red precipitate-like separation.

[0049] This process is the process of dopamine coating, that is, dopamine undergoes self-polymerization under weak alkaline conditions and is coated on Fe 2 O 3 On the surface of the precursor, if too much dopamine is added or the stirring time is too long, the thickness of the nitrogen-doped carbon layer will be too large, thus affecting the cycle rate performance. If too little dopamine is added or the stirring time is too short, the nitrogen-doped carbon layer will not be coated.

[0050] In some embodiments, in step S2, Fe 2 O 3 @PDA is dried at a constant temperature of 60℃~80℃ for 5~10h;

[0051] In some embodiments, in step S3, Fe 2 O 3 @PDA and Se powder are placed at both ends of the porcelain boat in a mass ratio of 1:4-8;

[0052] In some embodiments, in step S3, a 2 O 3 @PDA and Se powder in a porcelain boat filled with Ar / H 2 In a tubular furnace with a (95%:5%) atmosphere, the temperature was kept constant at 500-600°C for 4-6 hours, and the heating rate was controlled at 1-5°C / min for selenization treatment. Finally, FeSe with a hollow ring shape was obtained. 2 @NC Composites.

[0053] In another embodiment of the present application, the present application proposes a hollow ring-shaped FeSe 2 @Application of NC composite materials, composite materials as sodium ion negative electrode active materials.

[0054] Example

[0055] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0056] Embodiment 1:

[0057] A hollow ring FeSe 2 @NC composite material and its preparation method:

[0058] 3.84 mmol of ferric chloride hexahydrate was added to 160 mL of deionized water and stirred. After fully dissolved, 0.176 mmol of sodium sulfate and 0.04 mmol of sodium dihydrogen phosphate dihydrate were added. After stirring until a uniform mixed solution was formed, the mixture was transferred to a 200 mL reactor and placed in an oven. The reaction was carried out at 220 ° C for 12 h to obtain a precipitate. The precipitate was washed by centrifugation with deionized water and alcohol for several times and finally dried to obtain a hollow ring structure of Fe 2 O 3 The precursor was set aside. Prepare 100 mL of a buffer solution containing Tris, adjust the pH value of the solution to 8.5 by controlling the amount of Tris added, accurately weigh 100 mg of the precursor and dissolve it in the buffer solution, disperse it ultrasonically for half an hour, and then add 60 mg of dopamine (PDA) at a mass ratio of 1:0.6 between the precursor and dopamine. After continuous stirring for 12 hours at a constant temperature of 30°C, wash and centrifuge with deionized water and ethanol several times, and then put the precipitate obtained by centrifugation into a blast drying oven set at a temperature, keep it at 70°C for 6 hours, and dry it to obtain Fe 2 O 3 @PDA. The prepared Fe 2 O3 PDA and Se powder were placed at both ends of the porcelain boat in a mass ratio of 1:6 and placed in a chamber filled with Ar / H 2 The nitrogen-doped carbon-modified hollow ring FeSe was obtained by heating the FeSe nanostructured carbon ... 2 @NC composite material, namely FeSe 2 @NC Composites.

[0059] Embodiment 2:

[0060] A hollow ring FeSe 2 @NC composite material and its preparation method:

[0061] Example 1 was repeated with the following differences: 100 mg of the precursor was accurately weighed and dissolved in a buffer solution, ultrasonically dispersed for half an hour, and then 80 mg of dopamine (PDA) was added at a mass ratio of 1:0.8 between the precursor and dopamine. After continuous stirring for 12 h in a constant temperature environment at 30° C., the mixture was washed and centrifuged with deionized water and ethanol several times, and the precipitate obtained by centrifugation was placed in a blast drying oven set at a temperature, kept at 70° C. for 6 h, and dried to obtain Fe 2 O 3 @PDA. The prepared Fe 2 O 3 PDA and Se powder were placed at both ends of the porcelain boat in a mass ratio of 1:6 and placed in a chamber filled with Ar / H 2 The nitrogen-doped carbon-modified hollow ring FeSe was obtained by heating the FeSe nanostructured carbon ... 2 @NC composite material, namely FeSe 2 @NC Composites.

[0062] Embodiment 3:

[0063] A hollow ring FeSe 2 @NC composite material and its preparation method:

[0064] Example 1 was repeated with the following differences: the prepared Fe 2 O 3 PDA and Se powder were placed at both ends of the porcelain boat in a mass ratio of 1:6 and placed in a chamber filled with Ar / H 2 In a tube furnace with a (95%:5%) atmosphere, the temperature was kept constant at 550°C for 5 h, and the heating rate was controlled at 5°C / min. Finally, nitrogen-doped carbon-modified hollow ring FeSe 2 @NC composite material, namely FeSe 2 @NC Composites.

[0065] Comparative Example 1:

[0066] The comparative example is basically similar to the embodiment, but the difference is that the Fe 2 O 3 The precursor and Se powder were placed at both ends of the porcelain boat in a mass ratio of 1:6 and placed in an Ar / H 2 In a tube furnace with a (95%:5%) atmosphere, the temperature was kept constant at 550°C for 5 h, and the heating rate was controlled at 2°C / min. As a comparison, FeSe 2 Material.

[0067] Preparation and assembly of electrodes: The active material slurry consists of active material, conductive carbon (Super-P) and polyvinylidene fluoride as a binder in a mass ratio of 7:2:1. The active material slurry is fully ground and coated on copper foil to prepare a working electrode. After vacuum drying and rolling, the circular electrode piece is cut into pieces with a diameter of 12 mm. Pure metallic sodium sheet is used as the counter electrode and assembled into button cells in a glove box filled with argon. The diaphragm model is Celgard2325.

[0068] Structural characterization: The material phase analysis and crystal structure analysis were performed using a Bruker-D8-Advance X-ray diffractometer (XRD), and the sample morphology and microstructure analysis were performed using a Hitachi High-Tech SU8010 series super-resolution field emission scanning electron microscope (SEM).

[0069] Electrochemical performance characterization: The electrochemical performance of the material was characterized by constant current charge and discharge test using the Blue Battery Test System (CT3002CA), and the voltage window of the electrochemical test was fixed at 0.1-3 V. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed using a Swiss Metrohm electrochemical workstation (Autolab PGSTAT302N), with a scan rate of 0.1 mVs -1 , the frequency range is 100kHz~0.1Hz.

[0070] Structural characterization:

[0071] By XRD ( Figure 1 ) for the precursor Fe 2 O 3 The crystal structure was characterized and the spectrum of the synthesized precursor was compared with that of Fe 2 O 3 The standard card (PDF#89-0597) was compared and it was found that the positions of each characteristic diffraction peak were consistent with the standard card, indicating that Fe 2 O 3 The precursor was successfully prepared. SEM characterization showed ( Figure 2 )The precursor prepared by this method presents a hollow ring structure.

[0072] Experimental Example 1:

[0073] In order to compare the phase structures of the original sample and the modified sample, the FeSe 2 and FeSe 2 @NC composite material crystal structure, the XRD spectra of the two are as follows Figure 1 and 4 The XRD diffraction peaks of the two are similar to those of FeSe 2 The standard card (PDF#79-1892) is compared to the characteristic diffraction peaks at each position in the spectrum, indicating that pure FeSe was successfully prepared by a simple hydrothermal synthesis and controlled vapor phase selenization method. 2 and FeSe 2 @NC Composites.

[0074] Experimental Example 2:

[0075] In order to further study the morphology and structure of the product, SEM technology was used to analyze the Fe 2 O 3 , Fe 2 O 3 @PDA, FeSe 2 @NC composite materials were characterized by morphology. Figure 3 This is the SEM picture of the precursor coated with dopamine hydrochloride. Figure 1 It was found that after being coated with dopamine, the surface of the precursor changed from smooth to rough, but the overall hollow ring structure of the material was still maintained. Figure 5 It is Fe 2 O 3 @PDA is transformed into FeSe via controlled vapor phase selenization 2 @NC SEM image shows that the material can still maintain its original hollow ring structure after selenization, which fully demonstrates that the outer carbon layer has a good stabilizing effect on the overall structure, greatly alleviating the volume change of the material during the charge and discharge cycle, thus showing excellent cycle stability. At the same time, due to the doping of nitrogen elements derived from dopamine, it is beneficial to increase the wettability of the electrolyte and the composite material during contact, providing a large number of active sites for sodium storage, and further accelerating the electronic conductivity rate of the material.

[0076] Electrochemical performance characterization:

[0077] The results of the above material structure and morphology characterization preliminarily confirmed that the present invention successfully prepared FeSe with a hollow ring structure through a simple hydrothermal synthesis and a controllable vapor phase selenization method. 2 In order to study the improvement of the electrochemical performance of the hollow ring structure designed by the present invention, this experiment used FeSe 2 With FeSe 2@NC composite materials were used for comparison, and performance tests were carried out in terms of rate performance, cycle performance, and AC impedance under the same experimental conditions, and the results were compared and analyzed.

[0078] Experimental Example 3:

[0079] In order to further verify the excellent electrochemical performance of the modified composite material, FeSe 2 and FeSe 2 @NC composite materials were tested for rate performance at different current densities. Figure 6 FeSe 2 and FeSe 2 @NC composite materials have a voltage window of 0.1-3.0V and a current density of 0.2A. -1 , 0.5A g -1 , 1A g -1 , 2A g -1 , 5A g -1 Under different current densities, FeSe 2 @NC composites exhibited excellent electrochemical performance. Under the same test conditions, the unmodified FeSe 2 The capacity is significantly lower than that of FeSe 2 @NC composite material, indicating that the nitrogen-doped carbon coating structure has a great improvement on the cycle stability of the composite material, while also improving the sodium storage performance of the material.

[0080] Experimental Example 4:

[0081] In order to further explore the electrochemical performance of the composite material at a higher current density, cycle tests were carried out on the materials before and after modification. Figure 7 It is FeSe 2 and FeSe 2 @NC composites at a current density of 5A g -1 The performance diagram of 200 cycles under the same conditions. It can be found that the modified FeSe 2 @NC composite material can still maintain 421.4mAh g after 200 cycles -1 The specific capacity of FeSe without modification 2 The material is unstable during the cycle. 2 The @NC composite material maintains a good hollow ring structure, which can be explained by its good structural stability. At the same time, the design of the nitrogen-doped carbon layer helps to alleviate the volume expansion during the cycle and slow down the capacity decay. The above cycle performance test further confirms that this hollow ring structure FeSe with carbon layer coating 2@NC composites have excellent cycle stability.

[0082] Experimental Example 5:

[0083] In order to further explore the effect of nitrogen-doped carbon layer on Na + Effect of diffusion kinetics on FeSe 2 and FeSe 2 @NC composite materials were tested for AC impedance in the frequency range of 100kHz to 0.1Hz. Figure 8 FeSe 2 and FeSe 2 The Nyquist spectrum of the electrode of the @NC composite material after the cycle test. The inset is the fitted equivalent circuit. It can be clearly seen that the Nyquist spectrum of the material before and after modification is composed of a typical semicircle in the high-frequency region and a slant line in the low-frequency region. Among them, the semicircle in the high-frequency region corresponds to the charge transfer resistance (R ct ), while the oblique line in the low frequency region is similar to Na + Warburg impedance of diffusion (W 1 ). The Nyquist spectrum is fitted into an equivalent circuit diagram for analysis. 2 and FeSe 2 @The charge transfer resistance (R ct ) are 21.1Ω and 7.41Ω respectively, which indicates that the interface impedance of the material is significantly reduced after being coated with the nitrogen-doped carbon layer, which is beneficial to promote the transmission of electronic charge inside the material, thereby showing more excellent electrochemical performance.

[0084] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A hollow ring-shaped FeSe2@NC composite material, characterized in that: The composite material consists of an outer nitrogen-doped carbon layer and inner FeSe2 nanoparticles wrapped therein, and the composite material presents a hollow ring structure.

2. A hollow ring-shaped FeSe2@NC composite material according to claim 1, characterized in that: The particle size of the composite material is 180-220 nanometers.

3. A method for preparing a hollow ring-shaped FeSe2@NC composite material, comprising the following steps: S1, synthesizing Fe2O3 precursor, adding the precursor into a buffer solution for ultrasonic dispersion, then adding dopamine into the solution and stirring at room temperature to obtain a brown-red precipitate-like separation; S2, washing the brown-red precipitate with deionized water and ethanol for several times and drying it in an oven to obtain Fe2O3@PDA; S3, Fe2O3@PDA and Se powder were placed at both ends of a porcelain boat and selenized in a tube furnace to obtain FeSe2@NC with a hollow ring structure.

4. The method for preparing a hollow ring-shaped FeSe2@NC composite material according to claim 3, characterized in that: In step S1, synthesis of Fe2O3 precursor: S11, add a certain amount of ferric chloride hexahydrate to deionized water and stir, add sodium sulfate and sodium dihydrogen phosphate dihydrate after fully dissolved, stir until a uniform mixed solution is formed, transfer into a 200mL reactor, put into an oven, react at 200-250°C for 8-12h to obtain a precipitate, wash with deionized water and alcohol by centrifugation several times, and finally dry to obtain a Fe2O3 precursor with a hollow ring structure.

5. The method for preparing a hollow ring-shaped FeSe2@NC composite material according to claim 4, characterized in that: The amount of ferric chloride hexahydrate added is 6.3-6.5 g / L, the amount of sodium sulfate added is 0.14-0.16 g / L, the amount of sodium dihydrogen phosphate dihydrate added is 28-31 mg / L, and the mass ratio of ferric chloride hexahydrate, sodium sulfate and sodium dihydrogen phosphate dihydrate added is 92-100:4-5:

1.

6. The method for preparing a hollow ring-shaped FeSe2@NC composite material according to claim 3, characterized in that: Step S1, adding the precursor to a buffer solution containing Tris with a pH value of 8.0-9.0 for ultrasonic dispersion; the Fe2O3 precursor and dopamine are in a mass ratio of 1:0.6-1.2, dopamine is added to the solution and stirred continuously at room temperature for 10-18 hours to obtain a brown-red precipitate isolate.

7. The method for preparing a hollow ring-shaped FeSe2@NC composite material according to claim 3, characterized in that: In step S2, Fe2O3@PDA is dried at a constant temperature of 60°C to 80°C for 5 to 10 hours.

8. The method for preparing a hollow ring-shaped FeSe2@NC composite material according to claim 3, characterized in that: In step S3, Fe2O3@PDA and Se powder are placed at both ends of the porcelain boat in a mass ratio of 1:4 to 8.

9. The method for preparing a hollow ring-shaped FeSe2@NC composite material according to claim 8, characterized in that: In step S3, the porcelain boat containing Fe2O3@PDA and Se powder is placed in a tubular furnace filled with Ar / H2 atmosphere, with H2 accounting for 5-10%; it is kept at a constant temperature of 500-600°C for 4-6 hours, and the heating rate is controlled at 1-5°C / min for selenization treatment, and finally a hollow ring FeSe2@NC composite material is obtained.

10. Use of a hollow ring-shaped FeSe2@NC composite material, the composite material according to claim 1 or 2 or the composite material obtained by the preparation method according to any one of claims 3 to 9 as a sodium ion negative electrode active material.